In vitro toxin production by Fusarium solani f. sp. piperis - Duarte,Maria de Lourdes R. (2003)
Fusarium solani f. sp. piperis (teleomorph: Nectria haematococca f. sp. piperis), causal agent of root rot and stem blight on black pepper (Piper nigrum), produces secondary metabolites with toxigenic properties, capable of inducing vein discoloration in detached leaves and wilting in transpiring microcuttings. Production of F. solani f. sp. piperis (Fsp) toxic metabolites reached a peak after 25 days of static incubation on potato sucrose broth at 25 ºC under illumination. Changes in the pH of the culture filtrate did not alter the effect of toxic metabolites. However, when the pH was changed before the medium had been autoclaved, a more intense biological response was observed, with an optimum at pH 6.0. Isolates that produced red pigments in liquid cultures were more efficient in producing biologically active culture filtrates than those which produced pink coloured or clear filtrates suggesting that these pigments could be related to toxigenic activity. Detached leaves of seven black pepper cultivars and Piper betle showed symptoms of vein discoloration after immersion in autoclaved and non-autoclaved Fsp culture filtrates indicating the thermostable nature of these toxic metabolites.